New Trends in Adventure Tourism: A Lesson from 6th International Adventure Conference, 30 January- 2 February 2018, Segovia, Spain - Khatri, Ishwar (Journal of Tourism & Adventure, 2018)
This article tries to assess new trends in adventure tourism with the review of 6th international adventure conference- 2018 organized by Adventure Tourism Research Association (ATRA). For the review, the ‘book of abstracts’ which includes 41 abstracts of papers is studied and analyzed to come up with the findings and gaps in the studies. The study found some new trends and ideas in adventure tourism related to adventure activities, adventure challenges and adventure travelers’ motivation. Further, the article identifies gaps in the conference papers and suggest applicable research areas for extending and developing the subject area in such future events.